ESTIMATED POTENTIAL FOR ABANDONED LOST AND DISCARDED FISHING GEAR FROM CRAB FISHERIES BASED IN PPN MUARA ANGKE JAKARTA - Ronny Irawan Wahju; Am Azbas Taurusman; Mochammad Riyanto; Dhita Widhiastika; Asyifah Safitri (Jurnal Penelitian Perikanan Laut (Albacore), 2026)
Crab gillnet is a fishing gear intended for catching crabs that have the potential to cause Abandoned, Lost, and Discarded Fishing Gear (ALDFG). This research aims to estimate the potential for ALDFG and waste supplies from crab gillnet fisheries and to identify the causes and mitigation efforts. Data collection was carried out using survey methods and field observations, then the data were analysed descriptively. The research results show that the estimated lost crab gillnets potential in 1 month was 16 units (320 pieces) with a total weight of 1,137 kg. Meanwhile, in 1 year it is estimated that there will be 166 units (3.320 pieces) with a total weight of 11.375 kg or with a total loss value of IDR 573,750,000. The estimated abandoned crab gillnets potential in 1 month was 0.3 units (6 pieces) with a total weight of 23 kg, while in 1 year it is estimated that there will be 3 units (60 pieces) with a total weight of 230 kg and a loss of IDR 14,500,000. This study proposes a mitigation efforts including dissemination of the negative impacts of ALDFG and ghost gear, reporting program of lost fishing gear, providing incentives and implementing gear marking. Key words: ALDFG, debris, fishing gear, gillnet, PPN Muara Angke